Religion og historie på Balkan - Carsten Riis (Religionsvidenskabeligt Tidsskrift, 1994)
The article gives a survey of selections from recent literature and a few older, classic works on the history of the religions, i.e. Christianity, Islam and Judaism in the Balkans (except Turkey). the article puts a special emphasis on literature dealing with the connection between the religions and the political and social history. This is followed by a comment on national mythologies in the Balkans and an interoduction to the literature on the history of this region. the conclusion evaluates the role of the religions in the present Balkan conflicts; t he religions are not curcial and the conflicts are not religious wars but because of the importance of religion in ethnic classification, the religions become parts of the nationalist power game.